Diabetes self-management and its influencing factors among adults with type 2 diabetes mellitus in rural Sri Lanka: A cross-sectional study - Premadasa, Samantha Sandamali; Masingboon, Khemaradee; Samartkit, Niphawan (Belitung Raya Foundation, Indonesia, 2024)
Background: Diabetes Self-Management (DSM) is pivotal in managing diabetes. However, poor engagement in DSM has been observed in rural Sri Lankan settings. Thus, identifying factors influencing DSM is crucial for nurses and other healthcare professionals. Objectives: This study aimed to describe DSM among adults with Type 2 Diabetes Mellitus (T2DM) in rural Sri Lanka and to examine whether perceived stress, health literacy, self-efficacy, and family support can predict DSM among adults with T2DM in rural Sri Lanka. Methods: This correlational predictive study used a simple random sampling technique to recruit 160 adults with T2DM from an outpatient clinic at a secondary care hospital in a rural area of Sri Lanka. Data were collected from March to April 2024 using socio-demographic and standardized questionnaires to examine predictive factors of DSM, including perceived stress, health literacy, self-efficacy, and family support. Data analysis was conducted using descriptive statistics and standard multiple linear regression analysis. Results: Approximately half of the participants had uncontrolled T2DM (Fasting Plasma Glucose (FPG) >126) and sub-optimal DSM. The analysis revealed that all variables could explain 39.3% of the variance in DSM among rural Sri Lankan adults with T2DM. However, DSM was significantly predicted by self-efficacy (β = 0.530, p = 0.001), harmful family involvement (β = -0.169, p = 0.038), and health literacy (β = -0.162, p = 0.020). Conclusion: The findings emphasized the need for further development of interventions to increase self-efficacy and reduce harmful family involvement to enhance DSM among adults with T2DM. Nurses and other healthcare providers should target family members’ engagement to improve self-efficacy among this population.